Optimal Control Strategies for the Population Management of the Bali Starling: A Mathematical Modeling Approach - Gandhiadi, G.K.; Tastrawati, N.K.; Gautama, P.W.; Dharmawan, K. (The Indonesian Bio-Mathematical Society, 2025)
The Bali Starling (Leucopsar rothschildi), an endemic species of Bali, faces severe threats from habitat loss, poaching, and environmental changes, necessitating effective conservation strategies. This study presents a mathematical model to describe the population dynamics of the Bali Starling within the breeding center at USS Tegal Bunder, TNBB, integrating optimal control theory to improve conservation efforts. The model incorporates key biological factors such as growth, transfer, and habituation processes, and utilizes Pontryagin’s Maximum Principle to determine an optimal control strategy that balances population sustainability with resource efficiency. Numerical simulations compare controlled and uncontrolled scenarios, highlighting the impact of different control cost weights (q) on population management. The results suggest that moderate control interventions (q = 0.06 − 0.10) are most effective, ensuring sustainable population growth while min- imizing intervention costs. These findings provide valuable insights for optimizing captive breeding programs and offer a scientific basis for adaptive conservation strategies to protect endangered species like the Bali Starling.